2021
DOI: 10.3390/nu13051645
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk from Previously COVID-19-Infected Mothers: The Effect of Pasteurization on Specific Antibodies and Neutralization Capacity

Abstract: Background: Since the outbreak of coronavirus disease 2019 (COVID-19), many put their hopes in the rapid availability of effective immunizations. Human milk, containing antibodies against syndrome coronavirus 2 (SARS-CoV-2), may serve as means of protection through passive immunization. We aimed to determine the presence and pseudovirus neutralization capacity of SARS-CoV-2 specific IgA in human milk of mothers who recovered from COVID-19, and the effect of pasteurization on these antibodies. Methods: This pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
60
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 32 publications
(35 reference statements)
7
60
0
2
Order By: Relevance
“…Consistent with previous reports [21], we found high variability in human milk SARS-CoV-2-specific IgA levels in previously infected participants, with some of them having no milk conversion over the entire study period. In contrast, almost all vaccinated participants showed milk conversion.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous reports [21], we found high variability in human milk SARS-CoV-2-specific IgA levels in previously infected participants, with some of them having no milk conversion over the entire study period. In contrast, almost all vaccinated participants showed milk conversion.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are in line with previous research on serum where IgA levels were similar following infection or vaccination [18]. In human milk, the IgA response was studied separately following infection or vaccination [19][20][21], but only a few studies compared both exposure types longitudinally. In one study, higher IgA levels were observed in human milk of previously infected participants at day 12 versus those in vaccinated participants 47 days after receiving the first dose [22].…”
Section: Discussionsupporting
confidence: 90%
“…Research to date suggests that severe acute respiratory syndrome coronavirus 2 (SARS-Cov-2) is not transmitted in breast milk [1][2][3]. Instead, there is evidence that antibodies to SARS-Cov-2 isolated in breast milk have a strong immunological response against the virus [4][5][6]. Therefore, it is globally recommended that women continue to breastfeed to improve their infants' health and immunity during the pandemic [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…For example, 94% of human milk samples from lactating parents who recovered from COVID-19 exhibited pseudo-neutralization activity, while only 18% exhibited neutralization activity against wild-type virus. 7 Herein, we compare the temporal pattern and neutralizing activity of anti-SARS-CoV-2 antibodies in human milk following natural COVID-19 infection vs SARS-CoV-2 mRNA vaccination. We further assessed human milk ability to neutralize live wild-type virus from each group.…”
mentioning
confidence: 99%